Pengaruh Industri Batubara Terhadap Polusi Udara dalam Keseimbangan World Air Quality Index in India - Krisma Trianisa; Eko Priyo Purnomo; Aulia Nur Kasiwi (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2020)
The research was conducted on the researcher's curiosity on various environmental problems that arise as a result of the condition of the earth that is no longer able to sustain all the needs and desires of humans are infinite. But to avoid too much discussion, research will focus on how coal's role in contributing to high levels of air pollution in India. Air pollution is one of the environmental problems that often gets the world's attention. Talking about air pollution must be very closely related to the State of India, whose position as the country with the worst levels of pollution in the world. The method in this study uses a type of qualitative method with the source of data in the form of a literature review that is journal articles that have relevance to the research topic. The data obtained through the literature review will then be carried out data analysis with data reduction stages, data presentation and drawing conclusions. Based on the results of the study it can be seen that coal is the belle of fuel used by India as a support for the large energy needs of Indian society. Indeed, coal's natural resources have a positive impact on the economic situation and conditions of energy security in India, but there are more urgent things that need attention that is related to the negative impact of coal use in the form of pollution which is very dangerous for the survival of Indian society. Therefore, to protect the public from the worsening air conditions in India requires serious efforts from various groups, especially the government